Filling the Hole in the Nuclear Future: Art and Popular Culture Respond to the Bomb - Jacobs, Robert (Lexington Books, 2010)
From the dawn of the atomic age, art and popular culture have played an essential role interpreting nuclear issues to the public and investigating the implications of nuclear weapons to the future of human civilization. Political and social forces often seemed paralyzed in thinking beyond the advent of nuclear weapons and articulating a creative response to the dilemma posed by this apocalyptic technology. Art and popular culture are uniquely suited to grapple with the implications of the bomb and the disruptions in the continuity of traditional narratives about the human future endemic to the atomic age. Filling the Hole in the Nuclear Future explores the diversity of visions evoked in American and Japanese society by the mushroom cloud hanging over the future of humanity during the last half of the twentieth century. It presents historical scholarship on art and popular culture alongside the work of artists responding to the bomb, as well as artists discussing their own work. From the effect of nuclear testing on sci-fi movies during the mid-fifties in both the U.S. and Japan, to the socially engaged visual discussion about power embodied in Japanese manga, Filling the Hole in the Nuclear Future takes readers into unexpected territory